Agmatine inhibits the proliferation of rat hepatoma cells by modulation of polyamine metabolism - Gardini, Giulia; Cravanzola, Carlo; Autelli, Riccardo; Testore, Giovanni; Cesa, Roberta; Morando, Laura; Solinas, Sandro Paolo; Muzio, Giuliana; Grillo, Maria Angelica; Colombatto, Sebastiano (Journal of hepatology, 2003)
Background/Aims: Previous experiments have shown that agmatine, the product of arginine decarboxylase, is transported in competition with putrescine into quiescent rat hepatocytes, where it promotes several effects, including marked decrease of intracellular polyamines and induction of apoptosis. The primary aim of the present study was to assess the action of agmatine on transformed and proliferating hepatic rat cells. Methods: To assess the effect of agmatine on hepatoma cells, analysis by flow cytometry, Western blotting, reverse transcription–polymerase chain reaction, scanning and transmission electron microscopy, immunofluorescence detection of β-actin and α-tubulin were performed. Results: The results showed that agmatine has antiproliferative effects on the cell lines studied (HTC, JM2, HepG2). Further experiments were performed on HTC cells. The effect was proportional to agmatine concentration (in a range between 50 and 500 μM). It was not correlated with induction of necrosis or apoptosis and was accompanied by accumulation in G 2/M cell cycle phase and by dramatic modification of cell morphology. Spermidine reversed these effects, suggesting that the marked decrease of the polyamine pool is the main target of agmatine. Conclusions: The results obtained show a relationship between the decrease of intracellular polyamine content, the rate of cell growth and the cytoskeleton organization.